Design of an Arduino Based Automatic Sealing Machine with DS18B20 Sensor for Smart Temperature Control - Dewi, Marysca Shintya; Marlinda, Linda; Komarudin, Komarudin (Information Technology and Science (ITScience), 2025)
Sealing quality is a critical concern for Micro, Small, and Medium Enterprises (MSMEs) that rely on conventional machines lacking temperature control mechanisms. These systems often result in overheating or poor bonding, especially when applied to thin plastic materials such as polyethylene (PE), polypropylene (PP), and oriented polypropylene (OPP), each with varying melting points. This research aims to design an Arduino Uno-based automatic horizontal sealing machine integrated with a DS18B20 temperature sensor to provide smart temperature control during the sealing process. The proposed system employs a threshold-based ON-OFF control algorithm with a hysteresis margin of ±2.5°C, and displays real-time thermal feedback on a 16x2 LCD. The experimental methodology includes temperature deviation analysis and quality scoring of sealing results across PE, PP, and OPP films. Results show that the manual system deviated up to 15.4°C from the target temperature, leading to inconsistent outcomes. In contrast, the Arduino-based system maintained thermal stability within ±5°C and achieved a significant increase in sealing quality score from 60 to 92. These improvements indicate enhanced operational reliability, safety, and sealing consistency. The system provides a low-cost, scalable solution for MSMEs and can be upgraded to include PID control, IoT integration, or adaptive thermal profiling. This work demonstrates that embedded microcontroller-based automation is feasible and effective for small-scale packaging applications